The Role of Teachers in Developing Children's Responsibility Character in Group B2 At Asisi Onoboi Kindergarten - Fransisca ShellyYunita Asa (Early Childhood Education Development and Studies (ECEDS), 2022)
Character education is not new in human history. Parents in various ways, since a long time ago before there were formal educational institutions, have tried to educate their children to be good children according to the norms that apply in their culture. The main role of teachers in character education is teachers as educators, teachers, models and role models, motivators, and evaluators. So the researcher took a study on "the role of teachers in developing children's responsibility character in group B2 at Asisi Onoboi Kindergarten". The type of research used is qualititative research, with a total of 10 respondents divided into 3 interview respondents (teachers) and 7 observation respondents (students of Asisi Onoboi Kindergarten). Based on the results of the study there are three techniques used (storytelling, singing and giving assignments) which are seen from the role of the teacher as an educator.